2021
DOI: 10.1093/ehjcr/ytab308
|View full text |Cite
|
Sign up to set email alerts
|

A case report of an interrupted inferior vena cava and azygos continuation: implications for preoperative screening in minimally invasive cardiac surgery

Abstract: Background Femoral cannulation is commonly used in minimally invasive cardiac surgery to establish extracorporeal circulation. We present a case with a finding that should be evaluated when screening candidates for minimally invasive cardiac surgery. Case presentation A 57-year-old male patient was scheduled for minimally invasive repair of the mitral and tricuspid valve and a MAZE-procedure. During surgery there was difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Cetinkaya et al reported a case of a 61-year-old man with mitral and tricuspid valve replacement and an abnormal intraoperative IVC finding requiring conversion from a minimally invasive approach to a full sternotomy ( 5 ). Knol et al describe a similar case of a 57-year-old man with mitral and tricuspid insufficiency where a full sternotomy was also required after initially starting with a minimally invasive approach for valve reconstruction ( 6 ). In both cases, additional cannulation of the femoral vein was required for adequate venous drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Cetinkaya et al reported a case of a 61-year-old man with mitral and tricuspid valve replacement and an abnormal intraoperative IVC finding requiring conversion from a minimally invasive approach to a full sternotomy ( 5 ). Knol et al describe a similar case of a 57-year-old man with mitral and tricuspid insufficiency where a full sternotomy was also required after initially starting with a minimally invasive approach for valve reconstruction ( 6 ). In both cases, additional cannulation of the femoral vein was required for adequate venous drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The azygous vein is derived from the supra-cardinal [ 9 , 10 ]. Agenesis or failed fusion of these segments can lead to interruption of the IVC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, the patient may have an interruption of the IVC, which can complicate the procedure. Preoperative imaging, such as CT, can be used to confirm safe femoral cannulation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector row computed tomography (MDCT) and magnetic resonance imaging (MRI), are reliable non-invasive techniques for identifying IVC anomalies, accurately depicting the anatomy and variations of the IVC, and detecting any associated anomalies [ 3 ]. Additionally, physical examination and patient history, including polysplenia or a wide mediastinum, can also offer clues to IVC anomalies [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation